Keystone Flap for Reconstruction of Sacral and Ischial Pressure Injury - Tunjung, Narottama; Putri, Nandita Melati (Jurnal Plastik Rekonstruksi, 2021)
Introduction: Reconstruction of sacral and ischial pressure injury offers great challenges due to its high complication and recurrence rate. Providing durable tissue coverage with minimal donor site morbidity is paramount while ensuring fast operative time for the patients who often possess multiple comorbidities. This study aims to present cases of sacral and ischial pressure injury reconstruction using a keystone flap. Method: A retrospective study was performed by reviewing data from fifteen patients with a sacral and ischial pressure injury who underwent reconstruction using various types of keystone flaps in our center between 2019 and 2020. Results: The patients’ age ranged from 10 to 83 years old (average, 40.5 years old). The average wound dimensions were 9.4 ± 3.1 cm x 6.5 ± 2.7 cm and the mean area of the defects was 52.3 ± 35.7 cm2, with the largest defect was 15 x 12 cm (141.3 cm2). Mean operative time was 140 ± 24.5 minutes with nine wounds were reconstructed using type IV keystone flap (60%) and six patients using type IIA (40%). Postoperative complications occurred in three patients (20%). Other patients resulted in uneventful complete healing. Conclusion: The keystone flap is reliable, simple, has a fast technique, and minimal donor site morbidity to cover the defects of sacral and ischial pressure injury. Performing thorough debridement, choosing the right type of keystone flap, elevating the flap adequately to allow mobilization, preserving perforator “hotspots”, and suturing of the flap without tension are keys to achieve satisfactory results.